PENGARUH SEKTOR PARIWISATA DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP KESEMPATAN KERJA DAN KETIMPANGAN DISTRIBUSI PENDAPATANPENGARUH SEKTOR PARIWISATA DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP KESEMPATAN KERJA DAN KETIMPANGAN DISTRIBUSI PENDAPATANPENGARUH - Made Suyana Utama, Ni Made Eva Krismiyanti, (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
Inequality of income distribution is a problem that is often faced by each Regency/City in Bali. One of the mainstay sectors that is believed to be able to support the economy is the tourism sector so that efforts are needed in its utilization which are followed by improving quality of human resources in expanding employment opportunities so that people's income can be distributed evenly. This study aims to analyze influence of the tourism sector and the quality of human resources on employment opportunities and the unequal distribution of income in the Regency/Cities of Bali with 72 observation points in 2011-2018. Data analysis technique used is path analysis. Results shows that tourism sector and quality of human resources have a positive and significant effect on employment opportunities. Tourism sector, quality of human resources and employment opportunities have significant effect on inequality in income distribution. Tourism sector and the quality of human resources have an indirect effect on the unequal distribution of income through employment opportunities.